Constraints on the Variation of the Fine-structure Constant at 3 < z < 10 with JWST Emission-line Galaxies - Linhua Jiang; Shuqi Fu; Feige Wang; Sarah E. I. Bosman; Zheng Cai; Hyunsung D. Jun; Zhiwei Pan; Fengwu Sun; Jinyi Yang; Huanian Zhang (The Astrophysical Journal)
We present constraints on the spacetime variation of the fine-structure constant α at redshifts 2.5 ≤ z  < 9.5 using JWST emission-line galaxies (ELGs). The galaxy sample consists of 621 high-quality spectra with strong and narrow [O  iii ] λλ 4959,5007 doublet emission lines from 578 galaxies, including 232 spectra at z  > 5. The [O  iii ] doublet lines are arguably the best emission lines to probe the variation in α . We divide our sample into six subsamples based on redshift and calculate the relative variation Δ α / α for the individual subsamples. The calculated Δ α / α values are consistent with zero within 1 σ at all redshifts, suggesting no time variation in α above a level of (1–2) × 10 ^−4 (1 σ ) in the past 13.2 billion yr. When the whole sample is combined, the constraint is improved to be Δ α / α  = (0.2 ± 0.7) × 10 ^−4 . We further test the spatial variation in α using four subsamples of galaxies in four different directions on the sky. The measured Δ α / α values are consistent with zero at a 1 σ level of ∼2 × 10 ^−4 . While the constraints in this work are not as stringent as those from lower-redshift quasar absorption lines in previous studies, this work uses an independent tracer and provides the first constraints on Δ α / α at the highest redshifts. With the growing number of ELGs from JWST, we expect to achieve stronger constraints in the future.